2016
DOI: 10.4172/2471-9846.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Alzheimer's Disease Among Family Caregivers

Abstract: Objective: Although the majority of care for those with Alzheimer's is provided by informal rather than formal caregivers, family caregivers may lack knowledge about the disease. We sought to better understand the level and predictors of knowledge among family caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(78 reference statements)
3
2
0
Order By: Relevance
“…23 This study showed that the majority of caregivers were female (79.1%) and, in accordance with other studies, 68.1% of these were daughters of the patients. 23,24 In a comprehensive review of studies examining adherence to dementia medication, it was indicated that adherence ranged from 34% to 94%, consistent with the rate of adherence found in the first interview of this study (70.2%). One of the most important findings of this study is a 25.5% improvement in the rate of patients with high adherence to dementia medications after clinical pharmacist intervention.…”
Section: Discussionsupporting
confidence: 80%
“…23 This study showed that the majority of caregivers were female (79.1%) and, in accordance with other studies, 68.1% of these were daughters of the patients. 23,24 In a comprehensive review of studies examining adherence to dementia medication, it was indicated that adherence ranged from 34% to 94%, consistent with the rate of adherence found in the first interview of this study (70.2%). One of the most important findings of this study is a 25.5% improvement in the rate of patients with high adherence to dementia medications after clinical pharmacist intervention.…”
Section: Discussionsupporting
confidence: 80%
“…We found that participants have a misunderstanding about Alzheimer’s treatment benefits and how to deal with the patient. This finding is consistent with other studies (Eshbaugh and Stratton, 2016; Lee and Casado, 2019; Nielsen and Waldemar, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…This study also revealed that younger caregivers with higher education had a relatively higher level of knowledge. Previous studies showed similar results (Alhosis et al, 2012; Eshbaugh & Stratton, 2016). It seems that due to the lack of information provided about pressure injuries by healthcare providers, family caregivers should obtain the necessary information from other sources.…”
Section: Discussionsupporting
confidence: 80%